Diurnal differences in response to oral levodopa. Issue 11 (November 1990) - Frankel, J P; Pirtosek, Z; Kempster, P A; Bovingdon, M; Webster, R; Lees, A J; Stern, G M
Abstract : Diurnal differences in duration and quality of motor response to levodopa are frequently described by patients. The quality and duration of motor responses were objectively assessed to morning and afternoon oral levodopa doses in five patients with Parkinsonian motor fluctuations who complained of diurnal variation in response to their normal levodopa medication. Results suggest that under controlled conditions which eliminated the effects of diet and overlapping levodopa effects the response to levodopa remained unchanged throughout the day, and that the duration of response could be predicted by plasma levodopa levels.